Congenital Diverticular Disease of the Entire Colon. (11th April 2013) - Patel, A.; Joshi, H. M. N.; Kaur, C.; Wilson, J. M.
Abstract : Congenital or true colonic diverticulosis is a rare condition typified by the preservation of the colonic wall architecture within the diverticular outpouching. Cases of multiple jejunal diverticula have been reported as well as cases of solitary giant diverticula of the colon. There have been no reports in the literature of pancolonic congenital diverticulosis.